Spatial assessment of erosion and landslide hazards as indicators of land degradation in Solok Regency, West Sumatra - Dasrizal, Dasrizal; Juita, Erna; Wilis, Ratna; Febriandi, Febriandi; Febriani, Trina (Journal of Degraded and Mining Lands Management, 2026)
This study conducted an integrated spatial assessment to identify and map erosion and landslide threats, determining high-risk degraded areas in Solok Regency. The methods combined the Universal Soil Loss Equation (USLE) and the Analytic Hierarchy Process (AHP) within a Geographic Information System (GIS) framework. The analysis revealed a critical disconnect between erosion and landslide risks. Although 52.1% of the total area (?101,500 ha) was classified as safe from erosion (EHI<1), a substantial portion of this “safe” land-39.4% and 6.94% of the total area, respectively, exhibited moderate to high landslide susceptibility. Conversely, within the 37.1% of the area unsafe from erosion (EHI>1), moderate and high landslide susceptibility covered 24.3% and 7.4% of the total area, respectively. These results demonstrated that landslide triggers are independent of surface erosion processes in many areas, often occurring in locations considered "safe" from erosion due to innate geological and geomorphological factors. This complex interplay necessitates distinct yet coordinated mitigation strategies. The findings provide crucial spatial data for safe land use planning and disaster mitigation in Solok Regency, with a methodology applicable to other vulnerable landscapes, such as post-mining areas.